Material Analysis Supporting Cement Industry Muara Dua Area South Oku Regency South Sumatera - Desianto Payung Battu; Jamaluddin Jamaluddin; Fathony Akbar Praktikno (Universitas Muslim Indonesia, 2020)
Material cement industry are mostly formed by carbonate and silica. Geology of Muara Dua area was contain those material used in cement industry. Mineralogy of carbonate this area mostly formed by Calcium (Ca) contained on Calcite (CaCO3), Dolomite (CaMg(CO3)2) while Silica, Alumina, Iron Oxide element found as SiO2, Al2O3, Fe2O3, MgO on rock. Research area mostly generated by tectonically complex where the sedimentation mostly controlled the existence of material using in cement industry. Three analysis method were conducted which are Geological Mapping to describe macro petrology, Petrography analysis to determine mineralogy microscopic and Geochemical method using XRF to identified chemical mineralogy of rock. Limestone is one of lithology unit that develop on research area where known as Packstone to Wackestone (Petrography) while